EFFECT OF ETHNOCHEMISTRY INSTRUCTIONAL STRATEGY ON SECONDARY SCHOOL STUDENTS’ ACADEMIC ACHIEVEMENT AND RETENTION IN CHEMISTRY IN BAUCHI STATE NIGERIA - GARBA SHEHU; UGWUMBA AUGUSTINE OKORONKA (International Studies Journal)
The study investigated the effect of ethno-science instructional strategy (EEI) on senior secondary school students’ achievement and retention in chemistry. Three research questions and three hypotheses guided the study. The hypotheses were tested at 0.05 level of significance. The design of the study was pretest, posttest, and quasi-experimental experimental design. The population of the study was 20604 senior Secondary School year two (SS 2) chemistry students in Bauchi state, Nigeria. Multi-stage sampling technique was used at six levels in selecting the sample size of this study. One hundred and ninety-three (193) SS II chemistry students from four intact classes in four senior secondary schools made up the sample for the study. Chemistry Achievement Test (CAT) with Kuder-Richardson formula reliability index of 0.94 was used for data collection after validation by experts. Data were collected by administering the instrument as pretest and posttest after treatment of the groups. The data obtained were analyzed using mean, standard deviation and Analysis of Covariance (ANCOVA). The results showed that there is a significant difference in the mean achievement and retention test scores of students in the experimental and control groups in favour of the experimental group taught using EEI strategy. However, based on school location the instructional approach was successful in helping students retain and apply knowledge over time, irrespective of their school location. The study recommended that strategy improved senior secondary school academic achievement and retention irrespective of school location, hence it should be encouraged.